Analysis of Employee Performance at the Murung Raya Village Office, South Banjarmasin District - rukman, rukman (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study aims to find out and analyze the performance of employees at the Murung Raya Village Office, South Banjarmasin District. Design/methodology/approach: This study is a descriptive analysis. The population in this study is all employees at the Murung Raya Village office, South Banjarmasin District. Sample withdrawal uses a saturated sample technique, where all populations are respondents in this study. The analysis technique used is descriptive analysis. Findings: The results of the study can be concluded that employees are able to position their abilities in the tasks given by their superiors to complete and be responsible for all these tasks. Research limitations/implications: This research is limited to descriptive analysis so that researchers can further explore methods, techniques, and larger populations. Practical implications: The performance of the employees has also been categorized as very good, because the performance they do is in accordance with the expectations of the superiors and what is applied so that the performance carried out goes well, in accordance with the expectations of the superiors at the village office. Originality/value: This research is useful for the development of employee performance in the village. Paper type: Research paper